Sexing the “drop-drop” beetle, Psiloptera pertyi (Coleoptera: Buprestidae) - MOLINARIO DE SOUZA, RODOLFO; DOS ANJOS, NORIVALDO; DE NADAI, JANAÍNA; DINIZ SILVEIRA, RODRIGO; CORDEIRO, GLAUCIA (Revista Colombiana de Entomología, 2007)
The sexual description of adult Psiloptera pertyi was carried out through observations of their external morphological characteristics. Males have their first five abdominal sternites, as well as the seventh and eighth, strongly sclerotized. Females have a similar morphology except the eighth abdominal sternite is not sclerotized. Males have a prominent apex on the seventh sternite, while females have a deep incision in the apical margin of the same segment. Males also have a triangular incision en the extreme posterior margin of the fifth sternite; in females, this segment is rounded. The number and form of the abdominal sternites should be taken into account for sexing adults of P. pertyi.